2010
DOI: 10.1007/s11434-010-3072-z
|View full text |Cite
|
Sign up to set email alerts
|

Carbon isotopic composition, turnover and origins of soil CO2 in a monsoon evergreen broadleaf forest in the Dinghushan Biosphere Reservoir, South China

Abstract: Carbon isotopic compositions of soil CO 2 in rainy season (July) from two natural soil profiles (DHLS & DHS) in the monsoon evergreen broadleaf forest in the Dinghushan Biosphere Reservoir (DBR), South China, are presented. Turnover and origins of soil CO 2 are preliminarily discussed in this paper. Results show that the content of soil CO 2 varies between 6120 and 18718 ppmv, and increases with increasing depth until 75 cm, and then it declines. In DHLS, soil CO 2 δ 13 C ranges from −24.71‰ to −24.03‰, showi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…The δ 13 C-CO2 in the red soil below 50-60 cm tended to be stable; this finding is consistent with other studies in non-karst areas [29]. This stability with increasing soil depth may be attributed to the composition of stable carbon isotopes of CO2 produced from the soil or the limited impacts of the climate on the physical properties of deep soils.…”
Section: Soil Co2 Concentration and δ 13 C-co2 Affected By Karstificasupporting
confidence: 90%
“…The δ 13 C-CO2 in the red soil below 50-60 cm tended to be stable; this finding is consistent with other studies in non-karst areas [29]. This stability with increasing soil depth may be attributed to the composition of stable carbon isotopes of CO2 produced from the soil or the limited impacts of the climate on the physical properties of deep soils.…”
Section: Soil Co2 Concentration and δ 13 C-co2 Affected By Karstificasupporting
confidence: 90%
“…Generally, the contribution of root respiration to soil CO 2 emissions varies over a large range (<10% to >90%), with an overall mean of 48% as reported by Hanson et al (), who compiled data from 50 studies covering large areas of the globe. Ding et al () found that the contribution of root respiration to soil CO 2 emissions averaged >80% in densely vegetated parts of the evergreen broad lead forest, and the contribution was >90% in the upper 20 cm of soil, and decreased to 32% below 20 cm at sparsely vegetated sites in the Dinghushan area in southern China, geographically near to the study area. The phenomenon reported here, that root respiration contributed a large proportion of soil CO 2 in the catchment, is consistent with the observation that plants in karst areas tend to allocate more biomass in roots (Ni et al, ).…”
Section: Resultsmentioning
confidence: 89%
“…Therefore, it could be concluded that CO 2 in some lakes does not originate primarily from the input of soil organic matter from catchments, but from soil CO 2 . The CO 2 emissions in this kind of lake are one way that soil CO 2 returns to the atmosphere, although there are often small differences in isotopic compositions and ages of CO 2 between that evaded from waters and that evaded directly from soils (Leith et al, ) and between that produced in surface versus deep soils (Ding et al, ). This view is in accord with the conventional carbon cycle that blends outgassing from aquatic systems with terrestrial respiration (see Battin et al, ).…”
Section: Resultsmentioning
confidence: 99%